Peri-conceptual and antenatal parental factors and neonatal congenital heart disease: a case-control study - Zhang, Yi; Cheng, Yi; Zhao, Quming; Ma, Xiaojing; Hu, Xiaojing; Wang, Huijun; Sun, Lena; Kline, Jennie; Bellinger, David C.; Lo, Cecilia; Yan, Weili; Huang, Guoying (Pediatric Medicine, 2019)
Background: Our understanding of the causes of congenital heart disease (CHD), a leading cause of infant death in developed countries is poor. This study is aimed to explore the relationship between the occurrence of CHD in neonates and parental environmental exposures during peri-conceptual period. Methods: A case-control study was conducted at 9 maternity hospitals in eastern China. Cases comprised of neonates with CHD diagnosed by cardiac ultrasound. The controls were healthy infants who were born in the same center at the same period and in similar conditions. The neonates’ parents completed a questionnaire for collecting pre-conceptual environmental exposures including smoking, alcohol, supplementation of vitamins and folic acid, herbal medications, and medications during peri-conceptual period. Results: A total of 199 CHD cases and 262 controls were recruited without difference in gender and maternal age. Multivariable logistic regression analysis showed that maternal vitamin supplements (OR 0.57; 95% CI: 0.35–0.94) and folic acid-supplements (OR 0.64; 95% CI: 0.42–0.97) in the first trimester of pregnancy decreased the risk of CHD. Paternal smoking (OR 1.86; 95% CI: 1.22–2.85) and Chinese herbal medication intake (OR 3.46; 95% CI: 0.98–12.19) may increase the risk of CHD. Conclusions: The supplements of vitamin and folic acid in the early gestation would be important to decrease the risk of the occurrence of CHD. While the exposure to smoke may be a risk factor.